Explicit vs. Implicit Feedback for SU and MU-MIMO - Clerckx, B; Gil Kim; Junil Choi; Young-Jun Hong (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2010)
SU and MU-MIMO performance relies on accurate link adaptation in order to benefit from multi-user scheduling, beamforming, adaptive coding and modulation. Such accuracy highly depends on the type of the channel state information feedback. LTE-Advanced has defined two major types of feedback, i.e. implicit and explicit feedback. Implicit feedback makes some assumptions on the transmit precoding and receiver processing at the time of CSI and CQI feedback. The CSI is expressed in terms of a recommended precoder, commonly denoted as PMI. Explicit feedback refers to the feedback of channel information without making any assumption on the transmit and receiver processing. In this paper, we discuss pros and cons of such feedback mechanisms for both SU and MU-MIMO and compare performance of both approaches using system level simulations compliant with LTE-A system. It is shown that implicit feedback is the preferred feedback framework for both SU and MU-MIMO.